#### Answer

(5,3)

#### Work Step by Step

Multiply the second equation by 2, then add the equations to eliminate x.
$6x+4y=42\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 6x+4y=\ \ \ 42$
$-3x+3y=-6\ \ \ \ $multiply by -2$\ \ \ \ \ \ \underline{-6x+6y=-12}$
$\ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ \ 10y=\ \ 30$
Solve for y.
$10y=30$
$10y\div10=30\div10$
$y=3$
Substitute 3 for y in either equation and solve for x.
$6x+4(3)=42$
$6x+12-12=42-12$
$6x=30$
$6x\div6=30\div6$
$x=5$